KAJIAN PANDEMI COVID-19 TERHADAP PENDAPATAN USAHA KULINER DI BANDA ACEH - Putri Ismatur Rahmi; sartiyah Sartiyah (Fakultas Ekonomi dan Bisnis UNSYIAH, 2023)
AbstractThe purpose of this study is to analyze differences in income, business capital, operational costs, labor and working hours of the culinary business during and after Covid-19 in Banda Aceh. Determination of the sample using purposive random sampling technique with a total sample of 73 respondents and using the different test analysis method. This analysis uses the Wilcoxon Signed Rank test to test the mean differences of two non-parametric paired samples. The results showed that all variables experienced an increase after Covid-19 subsided. Variables that experienced an increase of more than 50 percent were income, business capital and own capital, operational costs for electricity and water costs, labor, and working hours. Business capital from third parties, government assistance, and operational costs in labor wages and rental costs have increased by around 20 percent in post-Covid-19. It is hoped that the government will pay more attention to implementing policies regarding venture capital assistance to MSMEs in the new normal or post-Covid-19 era. This is due to the low number of business actors who receive assistance from the government.Keywords: Covid-19 Pandemic, Culinary Business Income, Wilcoxon Test.